(untitled) (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
Author Miss Pratiksha P. Yawalkar, Lecturer, Department of Quality Assurance, Dr. Rajendra Gode Institute of Pharmacy, Amravati, Maharashtra, India Abstract Pharmaceutical chemistry links chemical principles with drug development, formulation, and clinical application. Drug structure fundamentally determines pharmacological activity through functional groups that influence receptor binding, with structural modifications strategically employed to enhance potency, selectivity, and pharmacokinetic properties. Chemical kinetics principles govern drug stability and degradation pathways, including hydrolysis, oxidation, and photolysis reactions, informing appropriate storage conditions, beyond-use dating, and formulation strategies to maximize shelf life. Quality control methodologies employ analytical techniques including chromatography, spectroscopy, and dissolution testing to verify identity, purity, and potency of pharmaceutical products, ensuring batch consistency and conformance with established specifications. Pharmaceutical salt forms represent deliberate modifications of parent compounds through acid-base chemistry, enhancing solubility, stability, and bioavailability of otherwise problematic drugs, with selection among hydrochlorides, sulfates, and other salt variations significantly impacting formulation characteristics and therapeutic outcomes. These chemical principles directly influence clinical medication use by determining drug behavior in biological systems, manufacturing techniques, storage requirements, and ultimately therapeutic effectiveness across various patient populations Keywords: Molecular Structure; Degradation Pathways; Analytical Methods; Chemical Stability; Bioavailability Modification VIEW PDF